One-Pot Synthesis of Diverse Anion-Binding Macrocycles - Baliarsingh, Biswaranjan; Madhavan, Nandita (Synlett, 2024)
A one-pot synthetic protocol to access a diverse library of diamide–diester macrocycles from the same starting materials is reported. The molecular symmetry can be readily tuned based on the reaction sequence, while the core structure can be varied using amino acids and aromatic building blocks. The first class of macrocycles with C2 axes in their molecular plane were obtained in 24 h with 40–70% yield, while another class with C2 axes perpendicular to the plane were synthesized in 18 h in 10–30% yield. The phenyl- and serine-derived macrocycles of the first class could bind acetate, chloride, and phosphate ions. These macrocycles can be functionalized with hydrophobic groups and potentially be used as ion transporters.
Keywords: macrocyclization; molecular recognition; supramolecular functional systems; receptors; synthesis design; one-pot synthesis